1994
DOI: 10.1093/brain/117.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate dehydrogenase deficiency. Clinical presentation and molecular genetic characterization of five new patients

Abstract: Fibroblast cultures from five patients with early onset severe encephalopathy and lactic acidosis were studied for evidence of pyruvate dehydrogenase (PDH) deficiency. Three males had significantly reduced activity (0.29-0.45 nmol/mg protein/min versus normal controls 0.7-1.1 nmol/mg protein/min); two females had PDH activity within the normal range. However, as the majority of cases of PDH deficiency result from defects in the X-linked E1 alpha subunit and both females had biased patterns of X-inactivation (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…This transition was reported as a pathogenic missense mutation in one female patient with convincing clinical presentation with family history of congenital lactic acidaemia, normal enzyme activity in cultured fibroblasts, and the skewed X-inactivation pattern (Matthews et al 1994). However, case 1 was homozygous for this transition and had normal PDH complex activity in cultured skin fibroblasts.…”
Section: Resultsmentioning
confidence: 94%
“…This transition was reported as a pathogenic missense mutation in one female patient with convincing clinical presentation with family history of congenital lactic acidaemia, normal enzyme activity in cultured fibroblasts, and the skewed X-inactivation pattern (Matthews et al 1994). However, case 1 was homozygous for this transition and had normal PDH complex activity in cultured skin fibroblasts.…”
Section: Resultsmentioning
confidence: 94%
“…A silent mutation introduced in the same position reduces the homology score to an even greater extent and resulted in a similar abnormal splicing pattern to that observed in the patient. Several other mutations involving the codon for tyrosine 243 in the PDHA1 gene have been described Matthews, et al, 1994), although these have not been reported to result in mis-splicing. These mutations do reduce the homology score of the putative SRp40 binding site at position c.727-732, but, unlike the nonsense and silent mutations studied here, they strengthen, rather than weaken the score of an overlapping 5' SRp40 site.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 42 mutations have only been found once,whereas 6 (R72C, R263G, R302C, S312fs, Q382fs, S388fs) have been observed more than twice. Interestingly, the latter are specific for one sex, except for one mutation (R378H), which has been found in both sexes (5 males and 1 female; the children died between ages 4-41 months; Hansen et al 1991;Matthews et al 1994;Chun et al 1995;.…”
Section: Discussionmentioning
confidence: 99%